PENGARUH ARUS KAS DAN LABA AUNTANSI TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR INDUSTRI OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BEI - bagus rahmat setiawan (Menara Ilmu, 2018)
This study discusses the effect of cash flow and accounting earnings on stock priceof manufaktur industry otomotif and component company listed in Indonesia StockExchange (BEI) in the period 2015-2017. The research data obtained from incomestatement, statement of cash flows and Stock Price.Sampling was purposive samplingmethod as many as 6 companies in accordance with predetermined criteria. The researchmethod used is the study hypothesis by analysis of correlation coefficients, multiple linearregression, t test, F test, the coefficient of determination and beta coefficients.The results ofcorrelation studies show that accounting earnings and operating cash flow has notcorrelation. Research by the t test to prove that only the accounting profit that influencestock prices, while operating cash flow has no effect. Research by the F test to prove thatthe independent variable simultaneous effect on stock prices. Test shows the coefficient ofdetermination of cash flow and accounting earnings on stock price of 52%.Keywords: cash flow, accounting earnings and stock prices